The Role of Social Media in Empowering the Involvement of Women in Information Technology: A Case Study of Al-Qalam and Umaru Musa Yar’adua Universities - Darma, Sanusi Abu; Aliyu, Farida; Kurfi, Shafi’u Abubakar (American International Journal of Social Science Research, 2018)
The under-representation of the women in the field of Information Technology (IT) in Nigeria has been closely observed over the last decade. One of the facts is that social media have been widely and intensively used in Nigeria, which is an effective way to empower women in the IT sector. This study aimed to investigate the role of social media in empowering the involvement of women in information technology. In order to achieve the objectives of this study the current study conducted a survey amongst the female students of Al-Qalam and Umaru Musa Yar’adua Universities and tried to find out how the use of social media is contributing to the growth of women involvement in the IT sector. For this purpose, a sample of 200 female students was taken from these Universities via convenience sampling techniques. The quantitative method was used to collect data for this study. The findings in this study revealed that there was a significant relationship between women’s awareness and the encouragement of women in the IT sector through the use of the social media. Besides, there was a significant relationship between the empowerment of women and the encouragement of women in the IT sector through the use of the social media. Hence, women’s awareness and empowerment of women through the social media encouraged the involvement of women in the IT sector. In addition, this study recommends that there is need to examine the relationship between women and social media in various sectors such as government, healthcare, aerospace and security in order to trace the real role of social media in empowering the involvement of women in information technology in Nigeria.